Effect of Different Organic Acids on Survival of Larvae and Control of Water Microflora in Milk fish (Chanos chanos) Hatchery System - Kumar, N. Ranjit; Kumar, P. Prasanna; Siddaiah, G. M.; Murugadas, V.; Basha, K. A.; Sivaraman, G. K.; Prasad, M. M. (Fishery Technology, 2018)
This study reports the use of organic acids (acetic,malic, formic and citric) in fish larval rearingsystems for survival and controlling the microfloraof rearing water. The milk fish (Chanos chanos) larvaewas treated for 10, 15, 30 and 60 min with sevenconcentrations (%) viz., 1, 0.2, 0.1, 0.075, 0.05, 0.025and 0.02 of organic acids respectively. The percentagesurvival was zero (1, 0.2, and 0.1% conc) for allthe organic acid at various time periods. Theeffective concentrations for treating fish larvae are0.05, 0.05, 0.025 and 0.075% concentrations of acetic,malic, formic and citric acid, respectively where100% survival was observed. Similarly, when thelarval rearing water was treated with differentconcentrations of same organic acids and timeperiod, complete inhibition of microbial flora wasobserved (1, 0.2 and 0.1% conc) for all organic acidsat various time periods. However, at concentrationsless than 0.1%, total bacterial count (TBC) andpresumptive Vibrio count (PVC) were found in therange of 3.19 to 5.75 and 2.22 to 3.58 log 10cfu ml-1. In contrast, TBC and PVC in control groupwere found in the range of 6.37 to 6.90 and 4.35 to4.74 log 10 cfu ml-1. The acid treatment withconcentrations of 0.075, 0.05 and 0.025 except formicacid at 0.025, 0.020 significantly (p